PPaanntt PPooppccoorrnn 11 A high yielding hybrid of Popcorn for cultivation - Singh, Narendra Kumar; Sahoo, Smrutishree (Indian Farming, 2021)
Based on high yield performance, popping quality and resistance to diseases, Pant Popcorn 1 was identified by a Varietal Identification Committee in 62nd Annual Maize Workshop held at Assam Agricultural University Jorhat (Assam) and released and notified by the Central Sub- Committee on Crop Standards, Notification and Release of Varieties of Agricultural Crops for cultivation in NHZ and PZ. Pant Popcorn 1 was tested in AICRP maize trials in kharif. However, it has also shown better adaptation, high grain yield and even better kernel quality when the crop was cultivated in rabi and spring season at Pantnagar. So its cultivation can also be extended in rabi and spring season when irrigation facility is available. Being a high yielding along with good popping attributes, Pant Popcorn 1 may prove to be a potential crop for farmers for maximizing returns from maize cultivation.